Her Blood Do Know: Tragic Curse in Marina Carr's Plays - Seval, Ayşem (My University, 2019)
Aristotle, in part XIII of Poetics, argues that "the best tragedies are founded on the story of a few houses... who have done or suffered something terrible." Classical tragedy repeatedly deals with curses on great families. The committing of an unspeakable act of violence such as filicide, matricide or parricide or overstepping a primal taboo such as cannibalism or incest often takes the form of a family curse, haunting the new generations and perpetuating itself. Moreover, the idea of the haunting memory of a traumatic experience tragically repeating itself over generations involves a half-knowing complicity of the characters to trigger the curse. Trauma theorists argue that unresolved psychic conflicts regarding emotional or physical abuse and silenced violent histories lead to the repetition of the cycle. Thinkers like Gabriele Schwab argue that both the victims and perpetrators of trauma pass on disavowed violent histories to their offsprings "not only through the actual memories or stories... but also through the traces of affect... that remains unintegrated and inassimilable"(14). Thus, affective memories play a role on the psychic trigger that results in the repetition of tragic p- curse. Transgenerational family curse seems to be a recurring theme in several of Marina Carr's plays both with classical and non-classical content. Carr's characters are arrested in the repetition of the cycle in the manner of classical tragedies where wounds never heal. Drawing from the ideas of trauma theorists such as Abraham and Torok, La Capra, and Gabriele Schwab this paper seeks to analyse this mechanism of half-knowing complicity in Carr's Portia Coughlan and By the Bog of Cats.